Gastroenteritis during infancy is a novel risk factor for allergic disease. Issue 35 (August 2019) - Pan, Hui-Hsien; Lue, Ko-Huang; Sun, Hai-Lun; Ku, Min-Sho
Abstract : Abstract: Antibiotics during infancy, delivery, and breastfeeding affect the intestinal microbiota in early life and is associated with allergic disease. Gastroenteritis (GE) during infancy also affects intestinal microbiota in early life, however, its relationship to allergic disease has not been investigated. Data of 45, 499 males and 49, 430 females, from birth to 5 years of age, were collected from a national database in Taiwan. Subjects were categorized into early GE (GE within 0–6 months) and non-early GE group (no GE within 0–6 months). The rates of asthma (AS), allergic rhinitis (AR), and atopic dermatitis (AD) over 5 years were evaluated and compared between the groups. In patients with AS, AR, and AD, the number of clinical visits and drug prescriptions for the allergic disease was also evaluated to assess the effect of early GE on allergic disease. After adjusting for the effect of GE in later life and other factors, the rates of AS [OR (odds ratio) 1.54, 95% confidence interval (CI) 1.48–1.60], AR [OR 1.49, 95% CI 1.45–1.54], and AD [OR 1.40, 95% CI 1.33–1.47] were higher in the early GE group than in the non-early GE group. The magnitude of the increase was higher in females than in males. In those with AS, AR, and AD, the number of clinical visits and drug prescriptions was not different between the early GE and non-early GE groups. In children with early GE, good control of GE in the following years lowered the rate of allergic disease. Early-life GE was associated with increased rates of AS, AR, and AD in later life and this was trend more prominent in females.